Antioxidant Activity of Total Phenols and Flavonoids Extracted from Echinops polyceras Roots Grown in Syria - Issa Al-Assaf; Mays Khazem (Iraqi Journal of Pharmaceutical Sciences, 2022)
Free radicals are products of normal cellular metabolism, they are unstable, short-lived, and highly reactive and the excessive production of them may cause numerous degenerative diseases like cancer. Antioxidants such as polyphenols have a protective role against free radicals. Echinops polyceras Boiss. is one of Echinops (Asteraceae) genus species that spread in Syria, Lebanon and Palestine. Phytochemicals found in this species roots have been extracted with gradient polarity solvents, and primary screening of the secondary metabolites was established. Then, the phenolic compounds content was determined with Folin-Ciocalteu reagent and flavonoids content with aluminum chloride reagent. The free radicals scavenging activity was evaluated for all extracts with DPPH• in a 96-well microplate. The selectivity study indicates that ascorbic acid and reducing sugars didn't exist in the extracts. The identification tests showed the presence of polyphenols like flavonoids and coumarins. The methanolic extract of the E.polyceras roots was the most effective scavengers of free radicals (84% in 30 min) with phenolic compounds content 575.5 mg GAE/g DE and flavonoids content 130 mg QE/ g DE, and the chloroformic extract was the least effective (45% in 30 min) with phenolic compounds content 222.5 mg GAE/g DE and flavonoids content 57.5mg QE/ g DE. In conclusion, the phenolic compounds and flavonoids from Echinops polyceras Boiss. are effective in free radicals scavenging and protecting from diseases caused by oxidative stress.